Analisis Pengaruh Pengeluaran Pemerintah terhadap Kualitas Sumber Daya Insani Perspektif Maqasyid Syariah: Bukti Empiris di Negara-Negara Berkembang OKI - sukran sukran; sulistya rusgianto; fasiha fasiha (Jurnal Ilmiah Ekonomi Islam, 2023)
The purpose of this study is to examine the impact of government expenditure on education and health on enhancing the quality of human resources in developing nations that are members of the OIC under maqasyid sharia. This study employs panel data and spans eight emerging nations (upper middle-income countries) from 2011 to 2020. The panel data model employed is the random effect model. The findings reveal that the variable of government spending on education has no effect on the growth of human resource quality. Government health investment has a considerable beneficial impact on the development of human resources in OIC emerging nations. When examined concurrently, government investment in education and health has a considerable beneficial effect on human capital development. Thus, long-term and coordinated investment in these two areas can bring significant rewards in terms of boosting human capital quality. According to maqasyid sharia, government expenditure in these two areas can assist individuals in achieving goals such as defending religion, soul, mind, children, and property in order to attain Falah